2008
DOI: 10.1088/0953-8984/20/33/335106
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Eu3+-, Tb3+-, Dy3+- and Tm3+-doped transparent GeO2–TiO2–K2O glass ceramics

Abstract: In this paper, we present the photoluminescence properties of Eu3+-, Tb3+-, Dy3+- and Tm3+-doped potassium–titanium–germanate glasses and glass ceramics. Following the x-ray diffraction measurement, the glass structure was established. Compared to Eu3+-, Tb3+-, Dy3+- and Tm3+-doped glasses, their respective glass ceramics show stronger emissions due to the presence of the K2TiGe3O9 crystalline phase. For Eu3+-doped glass and glass ceramics, five emission bands centered at 578 nm , 592 nm , 614 nm , 653 nm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…The energy levels of Eu 3 þ arise from the 4f n configuration and the emissions arising from f-f transitions yield sharp lines in the spectrum. The emission in Eu 3 þ corresponds to transitions from the excited state 5 D 0 level to the 7 F J (J ¼0, 1, 2, 3, 4, 5, 6) levels of the 4f 6 configuration [13].…”
Section: Resultsmentioning
confidence: 99%
“…The energy levels of Eu 3 þ arise from the 4f n configuration and the emissions arising from f-f transitions yield sharp lines in the spectrum. The emission in Eu 3 þ corresponds to transitions from the excited state 5 D 0 level to the 7 F J (J ¼0, 1, 2, 3, 4, 5, 6) levels of the 4f 6 configuration [13].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, for CaMoO 4 :Dy 3+ single crystals, the decay curves measured in the 10-170 K temperature range are not exponential and obey the Inokuti -Hirayama model for energy transfer for an electric quad- rupole -quadrupole interaction in the absence of diffusion among the donors [15]. Recently, we reported spectral results of various 1 mol% RE ions-doped oxyfluoride glasses/glass ceramics [16][17][18][19][20][21], in which the room temperature decay curves were well fitted to the single-exponential as in the present case. Recently, it is reported that in Er 3+ and Ho 3+ -doped nanocrystalline yttria, emission spectra obtained were with less intensity compared with bulk materials.…”
Section: Dysprosium (Dy 3+ )mentioning
confidence: 86%
“…(2). Generally, when Eu 3 þ ions are excited to any level above the 5 D 0 , there is a fast non-radiative multiphonon relaxation to this level and the emission form 5 D J( ¼ 1-3) to 7 F J are several orders smaller than that of 5 D 0 to 7 F J [13]. The τ 1 and τ 2 are attributed by the fast process and slow process.…”
Section: Resultsmentioning
confidence: 99%